The Major Transitions in Evolution—A Philosophy-of-Science Perspective - Okasha, Samir (Frontiers in Ecology and Evolution, 2022)
In the wake of the pioneering works of Buss (1987) and Maynard Smith and Szathmary (1995) and Michod (1999), the study of major evolutionary transitions is now a thriving research program within evolutionary biology. In addition to its obvious scientific interest, this research program raises interesting philosophical questions. These fall into two categories: conceptual and ontological. The former category includes questions about what exactly an evolutionary transition is, what form an evolutionary explanation of a transition should take, and whether a general theory that applies to all transitions is possible. The latter category includes questions about the status of the higher-level units to which evolutionary transitions give rise (e.g. organism, superorganism or individual), and about the nature of the resulting hierarchical organization. Tackling these questions requires an integrative approach that draws on both biology and the philosophy of science.